2004
DOI: 10.1002/micr.20018
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical lip replantation: Evaluation of functional and aesthetic results of three cases

Abstract: Lip amputations are rare, and microsurgical replantation must be systematically tried to restore form and function in one step. The authors present a series of three cases. Revascularization of the amputated segment was obtained by arterial anastomosis with the corresponding labial coronary artery. No venous anastomosis was carried out, because no vein could be identified. Venous drainage was obtained by inducing bleeding and by postoperative application of leeches for 6 days. Anticoagulant therapy and antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The restoration of venous drainage could not be performed because there were no veins accompanying the labial artery. 16 Therefore, leech therapy was required for approximately 1 week until collateral circulation developed to support adequate venous drainage. In the absence of a suitable artery in the amputated segment, successful replantation can be performed in some instances using arterialized venous anastomosis technique, should a suitable vein in the amputated lip segment exist.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of venous drainage could not be performed because there were no veins accompanying the labial artery. 16 Therefore, leech therapy was required for approximately 1 week until collateral circulation developed to support adequate venous drainage. In the absence of a suitable artery in the amputated segment, successful replantation can be performed in some instances using arterialized venous anastomosis technique, should a suitable vein in the amputated lip segment exist.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest series, Walton et al 1 published a review of 13 replants from 12 institutions. Duroure et al 2 published a series of three cases in France and the remaining publications are single case studies. [3][4][5][6][7][8][9][10] In all, 24 cases of successful lip replantation have been reported in the English literature.…”
Section: Discussionmentioning
confidence: 97%
“…A large systematic review showed that 50% of patients receiving leech therapy also require blood transfusion . Among those receiving blood, transfusion requirements range from two to 29 units . For an individual patient, use of 350 leeches and transfusions of 29 units have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Leeches have been used to salvage many types of reconstructive procedures, including ear replantation, lip replantation, nasal skin avulsion, penile replantation, nipple congestion after elective breast surgery, and head and neck reconstruction . High salvage rates (>90%) of congested skin flaps and local flaps can be expected .…”
mentioning
confidence: 99%
See 1 more Smart Citation